The principle of individualization in foreign language learning - Jorayeva Yulduz Roziklovna (Peerian Journals Publishing, 2023)
In this article, we have considered in detail the methodological principles underlying these methods in order to understand what modern methods of foreign language teaching are based on. In addition, we talked about the principles of individualization and communicative education.
Keywords: Individual; principles of communicative education; methodology